P1_7 Row, Let’s Row Away - East, Oliver; Longstaff, Emma; Li, Chak; Fletcher, Mark (Physics Special Topics, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–>This paper investigates the potential, energy difference between flying to a destination, compared to rowing to it. i.e. the energy burned per passenger on an airplane, compared to a passenger rowing across the sea to the destination. The destinations we consider are from London Heathrow to New York JFK airport, and we found that for a Boeing 747 and an Airbus A380, the energy used is 6069.1 MJ and 5677.8 MJ respectively. The amount of energy to row the distance in a single lightweight scull was found to be 128.67 MJ; in comparison to the Airbus the rower uses approximately 98% less energy. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>